Preparing for protection of civilians in United Nations peacekeeping operations - Ross Allen; Frederik Rosén; Kristoffer Tarp (Danish Institute for International Studies (DIIS), 2016)
The important 2015 report of the High-Level Independent Panel on United Nations Peace Operations (HIPPO) identified the Protection of Civilians (PoC) as a "core obligation" of UN Peacekeeping. Yet PoC is not a standard military task. Most commanders and troops arriving to UN Peacekeeping missions need to learn about specific mission mandate requirements on PoC, and how, with only suboptimal equipment available, to operationalize these requirements in volatile and hostile environments. Training of peacekeepers and specifically pre-deployment training therefore sets UN Peacekeeping an enduring test. Presented with serious challenges, the inferior responses of peacekeepers related to the protecting civilians in a number of recent cases point to the need for a serious re-evaluation of training and training needs. This report presents the findings of a pilot-survey of Troop Contributing Countries to United Nations Peacekeeping Operations and their inclusion of training related to PoC in pre-deployment training. The findings indicate that national-level training efforts do not automatically embrace United Nations policy, guidance, and tactical level training resources. More broadly, PoC seems to be more of a consideration within pre-deployment training, rather than a defining strategic concept at the center of pre-deployment training. The report argues that if UN member states request PoC to stand as a "core obligation" of UN Peacekeeping, UN member states and UN Department of Peacekeeping Operations / Department of Field Support need to do a better collective job in preparing the troops serving in UN Peacekeeping missions to implement mandate requirements on PoC.
Keywords: 300